Impact of Climate Change on Cardiovascular Disease Epidemiology: A Global Analysis - Gopisetty Harshitha; Jampani sathish Babu (Utilitas Mathematica, 2025)
This study investigates the relationship between climate change parameters and cardiovascular disease (CVD) epidemiology across global populations. Using meteorological data from 1990-2023 alongside comprehensive health records from multiple international databases, we developed a novel predictive framework that identifies significant correlations between environmental shifts and CVD incidence. Our model demonstrated that for each 1°C increase in average annual temperature, cardiovascular event risk increased by 4.7% (p<0.001), with particularly pronounced effects in urban areas and among vulnerable populations. Analysis of temporal trends revealed stronger associations in recent decades, suggesting adaptation mechanisms may be insufficient to counter accelerating climate effects. The proposed Climate-Cardiovascular Risk Assessment Framework (CCRAF) achieved 87.2% accuracy in predicting regional CVD pattern shifts, outperforming traditional risk models. These findings underscore the urgent need for climate-responsive healthcare planning and targeted interventions for at-risk communities.